Analisis Statistik dalam Pendugaan Curah Hujan Studi Kasus di DAS Ciliwung Hulu - Wahyu Samsudin (Jurnal Aplikasi Statistika & Komputasi Statistik, 2016)
Determining for distribution of rainfall is a very important part in determining the plans of rainfall in a region. This study used daily rainfall data in 1992-2009 from three rainfall stations,namely Gunung Mas, Citeko and Gadog. Thiessen polygon method is used to determine the average rainfall region. The distribution of rainfall is determined by using statistical analysis with Chi-Square test. Based on the results of distribution suitability testing by using Chi-Square (χr2) with significance (α) we obtained χr2 value of 6.50 while the χr2 table is 7.185. Since the calculated χr2< χr2 table, then the Gumbel distribution is eligible. So that the distribution pattern of the right to Ciliwung upstream is the Gumbel distribution. The amount of planned rainfall-plant the upstream Ciliwung watershed based on the Gumbel distribution for the return period of 2, 5, 10, 25, 50, and 100 years, respectively are 70.98 mm, 88.98 mm, 99.55 mm, 113.93 mm , 124.59 mm and 135.18 mm.